Etika Hakim dalam Menjaga Independensi Peradilan di Tengah Tekanan Publik Digital - Firman Syah; James Nur Esa R; Krisno Jatmiko; Setyo Utomo (AHKAM, 2026)
Although judicial independence has received attention in various legal studies, research specifically examining the role of judicial ethics as a safeguard against informal digital-based public pressure remains limited. This study aims to analyze the role of judicial ethics in maintaining judicial independence amid digital public pressure and identify the forms of pressure faced by judges when deciding cases that attract public attention. The study employed a normative legal method using statutory and conceptual approaches. The primary legal materials included the UUD NRI Tahun 1945, Undang-Undang Nomor 48 Tahun 2009 tentang Kekuasaan Kehakiman, and the Kode Etik dan Pedoman Perilaku Hakim (KEPPH), while the secondary legal materials comprised national and international scholarly journal articles. All legal materials were analyzed descriptively and analytically. The results indicate that judicial ethics serve as moral and professional guidelines for maintaining judges’ integrity, impartiality, and independence. The Bangalore Principles of Judicial Conduct and the KEPPH constitute the principal normative instruments for strengthening such independence. However, the accelerated circulation of information through social media has created new forms of digital public pressure, such as trial by social media, which increase judges’ psychological burden and necessitate stronger ethical oversight mechanisms. These findings contribute to the development of judicial ethics studies in the digital era while broadening the understanding of informal intervention in judicial proceedings. This study affirms that strengthening professional ethics and institutional protection is necessary to safeguard judicial independence from the pressure of digital public opinion. The implications of this study include a theoretical contribution to the literature on judicial ethics and practical implications for the Mahkamah Agung and Komisi Yudisial in designing mechanisms for the protection and ethical oversight of judges in the digital era. This study also opens opportunities for empirical research on judges’ direct experiences in dealing with digital public pressure.